(untitled) (International Seven Journal of Multidisciplinary, 2025)
The protection of the rights of children and adolescents is a topic of great social and legal relevance, especially in the state of Amazonas, where socioeconomic and cultural challenges intensify the vulnerability of this population. This study analyzes the work of the Center for Assistance to Victims and Vulnerable Individuals – NAVIV/Recomeçar, an initiative aimed at promoting and guaranteeing the rights of children and adolescents, assessing its effectiveness in light of the principles of Human Rights and the Statute of Children and Adolescents (ECA). This bibliographical research seeks to understand how the program’s actions contribute to the realization of these rights, identifying advances, limitations, and possible paths for improving public policies directed at childhood and adolescence. The results show that NAVIV/Recomeçar has played an important role in building a more efficient and humanized protection network, operating in an intersectoral manner and aligned with the principles of comprehensive protection and absolute priority. The jurisprudential analysis of state courts reinforces the importance of judicial action in demanding the enforcement of the rights established in the ECA, especially in the face of state omission. In addition, the incorporation of the debate on the Digital ECA expands the discussion to virtual environments, revealing new dimensions of child and adolescent protection. It is concluded that the strengthening of public policies directed at childhood and adolescence in Amazonas depends on continuous investment, institutional coordination, and political commitment. For future research, it is suggested to conduct longitudinal evaluations of the impact of NAVIV/Recomeçar, comparative studies among states in the Northern region, and analyses regarding the implementation of the Digital ECA in vulnerable territories.